Reaction Rate in an Evanescent Random Walkers System - Dr. Subhash Das (International Journal of Advanced Science and Technology, 1970)
The diffusion reaction models are ubiquitous in the description of physical, chemical or biological processes. The random walk scheme is a useful tool for these models. Recently, evanescent random walk models have received attention inlifetime processes. For example, in a laser photolysis shows a different asymptotic limit when compared with other walker models. A diffusion reaction model based on a one dimensional continuous time random walk with evanescent walkers is presented here. Here an absorption probability density(APD) and reaction rate are calculated in the Laplace domain.